Oriented Antibody Covalent Immobilization for Label-Free Impedimetric Detection of C-Reactive Protein via Direct and Sandwich Immunoassays - Adesina, Abiola; Mashazi, Philani (Frontiers in Chemistry, 2021)
The detection and monitoring of biological markers as disease indicators in a simple manner is a subject of international interest. In this work, we report two simple and sensitive label-free impedimetric immunoassays for the detection of C-reactive protein (CRP). The gold electrode modified with boronic acid–terminated self-assembled monolayers afforded oriented immobilization of capture glycosylated antibody (antihuman CRP monoclonal antibody, mAb). This antibody-modified surface was able to capture human CRP protein, and the impedance signal showed linear dependence with CRP concentration. We confirmed the immobilization of anti-CRP mAb using surface sensitive X-ray photoelectron spectroscopy (XPS) and electrochemical impedance. The oriented covalent immobilization of mAb was achieved using glycosylated Fc (fragment, crystallizable) region specific to boronic acid. The direct immunoassay exhibited a linear curve for concentration range up to 100 ng ml−1. The limit of detection (LoD) of 2.9 ng ml−1, limit of quantification (LoQ) of 9.66 ng ml−1, and sensitivity of 0.585 kΩ ng−1 ml cm−2 were obtained. The sandwich immunoassay was carried out by capturing polyclonal anti-CRP antibody (pAb) onto the CRP antigen immunoreaction. The impedance signal after pAb capture also showed linear dependence with CRP antigen concentration and acted as a CRP antigen detection signal amplifier. The detection of the CRP antigen using sandwich pAb immunoassay improved LoD to 1.2 ng ml−1, LoQ to 3.97 ng ml−1, and enhanced the sensitivity to 0.885 kΩ ng−1 ml cm−2. The real sample analysis, using newborn calf serum, showed excellent selectivity and % recovery for the human CRP ranging from 91.2 to 96.5%. The method was reproducible to 4.5% for direct immunoassay and 2.3% for sandwich immunoassay.